Why Production Function Analysis is Irrelevant in Policy Deliberations Concerning Educational Funding Equity - Fortune, Jim C. (Education Policy Analysis Archives, 1993)
Hanushek and Walberg use production function methodology to contend that there is no relationship between school expenditures and student achievement. Production function methodology uses correlational methods to demonstrate relationships between input and output in an economic system. These correlational methods may serve to hide rather than reveal these relationships. In this paper threats to the validity of these correlational methods for analysis of expenditure-achievement data are discussed and an alternative method of investigation is proposed. The proposed method is illustrated using data from two states (Ohio and Missouri). The method demonstrates relationships between expenditures and achievement that were overlooked by the production function method.